Active summers matter: Evaluation of a community‐based summertime program targeting obesogenic behaviors of low‐income, ethnic minority girls. Issue 143 (September 2014) - Bohnert, Amy M.; Ward, Amanda K.; Burdette, Kimberly A.; Silton, Rebecca L.; Dugas, Lara R.
Abstract : Low‐income minority females are disproportionately affected by obesity. The relevance of summer months to weight gain is often overlooked. Some evidence suggests that summer programming, such as day camps, may offer increased opportunities for structured physical activities resulting in less weight gain. This study examined the effectiveness of Girls in the Game, a six‐hour four‐week sports and fitness summer camp program, in increasing physical activity (PA) and reducing body mass index and media use. Statistically significant increases were observed in four physical activity measures including total PA, MVPA, average number of ten‐minute bouts of MVPA, and minutes participants spent in bouts of at least ten minutes of MVPA. This chapter highlights the importance of investigating the potential relationships among weight, physical activity, sedentary time, media use, and participation in summer camp programming.